Potensi FuMA stem cells, kombinasi fukoidan dan Bone Marrow Stem Cells (BMSCs), sebagai penatalaksanaan mutakhir pada Infark Miokard Akut - Agung Bagus Sista Satyarsa; Sang Ayu Arta Suryantari; Putu Gupta Arya Gumilang; Ni Nyoman Ayu Dewi (DiscoverSys Inc., 2019)
Introduction: Acute myocardial infarction (AMI) is the leading cause of death worldwide. One of the causes of high morbidity and mortality is progressive and irreversible nature of the disease and current treatments are still not optimal in resolving these problems. Thus, this paper aims to describe the potential effect of combination of fucoidan and bone marrow stem cells (namely FuMA stem cells) as the novel management of AMI.Method: The method used in our paper was literature searching by including the keywords of AMI, BMSCs, and fucoidan.Result: Fucoidan from brown seaweed has shown a great potential effect as anti-inflammatory, anti-coagulant, anti-atherogenic, anti-oxidant, and anti-fibrotic. It limits the infarct area and increases SDF-1, CXCR4 and Akt expression as well as LVEF. However, fucoidan has not been able to regenerate cardiomyocyte cells in AMI. It takes a combination of BMSCs that have been shown to prevent the expansion of infarction area and improve post-infarction function.Conclusion: Thus, FuMA stem cells hold a great potential novel therapy for AMI. Further studies are needed to unveil the potential of FuMA stem cells in AMI management.